Empirical Analysis of the Relationship between Cost Efficiency and Loan Loss Provision in Chinese Commercial Banks - LIN, TAORAN (2017)
Using the panel data from the year 2008-2015 of 54 Chinese commercial banks, this study verifies three hypothesis including income smoothing, capital management and the business cycle. Meanwhile, the relationship between cost efficiency, global financial crisis and loan loss provisions has also been discussed and proved by the regression models. The empirical analysis proves the hypothesis of income smoothing and procyclicality management while it cannot find the evidence of capital management in Chinese commercial banks. Moreover, the sample data cannot support the hypothesis that the cost efficiency can affect the loan loss provision. When the effect of global financial crisis was considered, the income smoothing behaviours cannot be proved by sample data but pro cyclicality management still exists according to this study.